As significações do formador de formadores sobre sua atividade profissional no âmbito da formação continuada em serviço - Ferreira, Rodnilson Luiz (2018)
The present study has the general objective to understand the significations of the “teachers educator" on their professional activity in the context of continuing in-service training, before, during and after participation in the Tutorship Program. For this, we analyzed and interpreted the meanings of the participants, three educators of the Zilda Arns Education Professionals Training Center in São Caetano do Sul, SP, on the professional development of the "teachers educator", produced in a meeting, through a discussion group with the subjects surveyed. The concept of continuing or permanent training (ALMEIDA, 2012; ANDRÉ, 2016; IMBERNÓN, 2009, 2010, 2011; LIBÂNEO, 2008; e PLACCO, 2015) has been widely disseminated in educational and academic contexts, and also in the context of the implementation of public policies for adult learning. In-service training is a prerequisite for lifelong learning and for the personal, cultural and professional development of the "teachers educator". It is in the work context that these professionals face and solve problems, elaborate and modify procedures, create and recreate work strategies and, with this, can promote transformations and changes in practices of the subjects. In Brazil, this discussion is recent, the Professional master of the post-graduate studies program in Education: Teacher education (Estudos Pós-Graduados em Educação: Formação de Formadores - Formep) of the Pontifical Catholic University of São Paulo (PUC-SP) is a pioneering initiative. The theoretical basis had as its starting point the theory of Vygotsky (2009) and his followers. Still other contemporary authors allowed the deepening and expansion of the studies in the area of Socio- Historical Psychology (AGUIAR, 2006; BOCK; GONÇALVES, 2009; AGUIAR; BOCK, 2016). The analysis and interpretation of the data produced occurred through the use of a procedure called "Nuclei of Signification", as proposed by Aguiar (2013) and Aguiar, Soares and Machado (2015). The interpretive and explanatory analyzes indicated constitutive and contributory elements of the " teachers educators" in the context of continuing in-service training, such as: collaborative training network; not having a dichotomous view in relation to Theory X Practice, Cognitive X Affective, Individual Formation X Collective Formation and Guiding Strategy X Facilitating Strategy; to guarantee principles such as: to guarantee principles such as: formative dialogue, questioning, active listening, being fully present, flexibility, commitment, partnership, negotiate meanings, intentionality, empathy, believe in others, collaborative spirit, work together and provide professional development; and be able to position oneself in relation to pertinent questions in the exercise of one's activity, such as: doubt X certainty, Intention X Impact, Advisor X Educator